(untitled) (Bangladesh Journal of Animal Science, 2014)
This research was conducted to test the feasibility of using date palm(Phoenix dactylifera L.) brown sugar as an alternative to refined cane sugar in preparing sweet dahi. Quality assessment tests were conducted on four different types of dahi prepared by adding different levels of date palm brown sugar, such as 10% (A), 12% (B), 14% (C) and 12% refined cane sugar (D, as control). All the samples were analyzed for organoleptic, chemical and microbiological qualities. The scores for smell and taste, body and texture, color and appearance, and total scores for four types of dahi samples showed significant differences at various levels (p<0.01 to p<0.05). It was found that scores for all the organoleptic parameters of sample B were the highest among the samples, whereas sample D obtained the lowest scores. Total viable count of bacteria and coliform count, and sugar content, ash content, and protein content were differed significantly (p<0.01). Contents for fat also showed significant difference (p<0.05), though dry matter content, % acidity, and pH value showed insignificant differences. It could be concluded that sample B (containing 12% date palm brown sugar) was the best in terms of organoleptic, chemical and microbiological qualities. DOI: http://dx.doi.org/10.3329/bjas.v43i1.19387 Bang. J. Anim. Sci. 2014. 43 (1): 62-67